2004
DOI: 10.1002/syn.20059
|View full text |Cite
|
Sign up to set email alerts
|

Potential of [18F]β‐CFT‐FE (2β‐carbomethoxy‐3β‐(4‐fluorophenyl)‐8‐(2‐[18F]fluoroethyl)nortropane) as a dopamine transporter ligand: A PET study in the conscious monkey brain

Abstract: A dopamine transporter (DAT) ligand 2beta-carbomethoxy-3beta-(4-fluoro-phenyl)-8-(2-[(18)F]fluoroethyl)nortropane ([(18)F]beta-CFT-FE) was synthesized and evaluated in comparison with [(11)C]beta-CFT in monkey brain using animal positron emission tomography (PET). [(18)F]beta-CFT-FE and [(11)C]beta-CFT were injected intravenously to conscious monkeys for a 91-min PET scan with arterial blood sampling for metabolite analysis. In the conscious state, [(18)F]beta-CFT-FE provided a peak about 20 min after the inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…The distribution pattern of [ 11 C]b-CFT was consistent with the previously reported DAT distribution determined in monkey brain with PET (Harada et al, 2004;Tsukada et al, 2001). There were no significant differences in the BP ND values of [ 11 C]b-CFT between baseline and ketamine administration in any brain regions ( Figure 2c).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The distribution pattern of [ 11 C]b-CFT was consistent with the previously reported DAT distribution determined in monkey brain with PET (Harada et al, 2004;Tsukada et al, 2001). There were no significant differences in the BP ND values of [ 11 C]b-CFT between baseline and ketamine administration in any brain regions ( Figure 2c).…”
Section: Resultssupporting
confidence: 90%
“…In conscious monkeys and animal, PET anesthetic doses of ketamine significantly alter the synthesis rate of dopamine (Tsukada et al, 2000). Although dopamine D 2 receptor binding was decreased (Ohba et al, 2009;Onoe et al, 1994;Tsukada et al, 2000), dopamine transporter (DAT) availability is increased in living monkey brains (Harada et al, 2004;Tsukada et al, 2001). Although an inhibitory effect of ketamine on SERT was reported in vitro (Martin et al, 1990;Nishimura et al, 1998;Zhao and Sun, 2008), no one has evaluated the effects of subanesthetic doses of ketamine on SERT in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…11 C]GR205171 studies, has been shown to moderately increase radioligand binding (Tsukada et al, 1999;Elfving et al, 2003;Harada et al, 2004). Both Hypnorm (VetaPharma Ltd.) and isoflurane anes- …”
Section: Syvä Nen Et Almentioning
confidence: 99%
“…Some of these have been evaluated preclinically and several are in clinical trials [12,13]. Radioligands synthesized from these compounds have been effective in vitro ligands for transporter binding [11,14,15] as well as PET ligands for in vivo imaging [16][17][18]. Furthermore, the structure-activity relationships of cocaine analogs have provided vital information to design specific molecular tools to characterize the structure and function of DAT, and to further explore its role in the pharmacology of cocaine.…”
Section: Introductionmentioning
confidence: 99%